The Effect of Shallot Peel Ethanol Extract in Reducing Kidney MDA Levels in Diazinon-induced Wistar Rats - Mukhammad Arif Hadi Khoiruddin; Dina Helianti; Muhammad Hasan; Rosita Dewi; Sheilla Rachmania (Faculty of Medicine, University of Jember, 2022)
Diazinon is an organophosphate pesticide often used by farmer. The residue of diazinon may contaminate agricultural products and if accidentally consumed in a long term, may potentially led to health problems such as kidney disorders. Shallot (Allium cepa) peel was recently proposed to help recover the kidney damage due to its high flavonoid antioxidant content. This study aims to determine the antioxidant effect of shallot peel extract in reducing oxidative stress caused by diazinon with malondialdehyde (MDA) level indicator on the kidney of Wistar rats (Rattus norvegicus). This research was a true experimental with an in-vivo posttest-only control group design. The 28 rats were divided using a simple random sampling technique. The groups were the control group (K0), the diazinon group (K1), SPEE (Shallot Peel Ethanol Extract) groups which are P1 (300 mg/kg BW), P2 (600 mg/kg BW), P3 (900 mg/kg BW), P4 (1200 mg/kg BW) and P5 (2400 mg/kg BW). At the end of the study, the MDA kidney levels was analysed using the TBARS method. Effective doses were found in 600 mg/kg BW/day, 900 mg/kg BW/day, 1200 mg/kg BW/day, and 2400 mg/kg BW/day. The optimal dose of shallot peel extract in this study was 600 mg/kg BW/day. This study showed the effectiveness of shallot peel extract in reducing kidney MDA levels in diazinon-induced Wistar rats. Keywords: shallot peel, diazinon, kidney MDA level